2017
DOI: 10.7150/thno.20919
|View full text |Cite
|
Sign up to set email alerts
|

Towards Translational ImmunoPET/MR Imaging of Invasive Pulmonary Aspergillosis: The Humanised Monoclonal Antibody JF5 Detects Aspergillus Lung Infections In Vivo

Abstract: Invasive pulmonary aspergillosis (IPA) is a life-threatening lung disease of hematological malignancy or bone marrow transplant patients caused by the ubiquitous environmental fungus Aspergillus fumigatus. Current diagnostic tests for the disease lack sensitivity as well as specificity, and culture of the fungus from invasive lung biopsy, considered the gold standard for IPA detection, is slow and often not possible in critically ill patients. In a previous study, we reported the development of a novel non-inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 31 publications
2
62
0
Order By: Relevance
“…Advances in radiological technologies also deserve mention. Use of Aspergillus-specific tracers (e.g., siderophores and monoclonal antibodies) for immuno-PET detection is investigated, but such approaches for NAIMIs are still lacking (146)(147)(148). The immuno-PET approach shows promise as a theragnostic tool in mold infections (148).…”
Section: Advances In Diagnostic Strategiesmentioning
confidence: 99%
“…Advances in radiological technologies also deserve mention. Use of Aspergillus-specific tracers (e.g., siderophores and monoclonal antibodies) for immuno-PET detection is investigated, but such approaches for NAIMIs are still lacking (146)(147)(148). The immuno-PET approach shows promise as a theragnostic tool in mold infections (148).…”
Section: Advances In Diagnostic Strategiesmentioning
confidence: 99%
“…Inhalation models have been already described since the early 90’s [58] and their value has been proven [59]. A model of intratracheal intubation with ventilation has also been described to trigger a better distribution of spores [12, 60]. Hence, we believe that such models should be better characterized to assess whether these should be adopted as the gold standard for pulmonary infection models.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging with antibodies has, until very recently, been the domain of cancer detection ( Mestel, 2017 ), with limited application in infectious disease diagnostics ( Rolle and Wiehr, 2017 ). However, recent studies have demonstrated the enormous potential of antibody-guided PET/MRI (immunoPET/MRI) technologies to dramatically improve the molecular imaging of viral ( Santangelo et al, 2014 ), bacterial ( Wiehr et al, 2016 ), and fungal ( Rolle et al, 2016 ; Davies et al, 2017 ) infections in vivo , with the real possibility of precision medicine for infectious diseases in the near future ( Jain, 2017 ). ImmunoPET/MRI marries functionality of PET with the specificity of mAbs and anatomical depiction of MRI.…”
Section: Aspergillosis Imaging With Monoclonal Antibody Jf5mentioning
confidence: 99%